Q. {f(1)=0f(n)=f(n−1)+2Find an explicit formula for f(n).f(n)=______________
Given base case and formula: We are given the base case f(1)=0 and the recursive formula f(n)=f(n−1)+2. To find an explicit formula, we need to express f(n) in terms of n without the need to calculate all previous function values.
Calculate first few values: Let's calculate the first few values to see if we can identify a pattern:f(1) = 0 (given)f(2) = f(1) + 2 = 0 + 2 = 2f(3) = f(2) + 2 = 2 + 2 = 4f(4) = f(3) + 2 = 4 + 2 = 6It seems that f(n)=2×(n−1).
Identify pattern: Let's check if our pattern holds for n=1:f(1)=2×(1−1)=2×0=0, which matches the given base case.
Check pattern for n=1: Now let's check if our pattern holds for n=2:f(2)=2×(2−1)=2×1=2, which matches the value we calculated earlier.
Check pattern for n=2: We can now generalize this pattern to find the explicit formula for f(n):f(n)=2×(n−1).